ANALISIS KOMPARATIF TERHADAP PERUBAHAN STATUS HARTA WAKAF: DALAM PERSPEKTIF IMAM SYAFI’I DAN HANAFI - Anggita Vela (LPPM STAI DARUSSALAM LAMPUNG, 2015)
Waqf is the release of the property that is represented from the ownerby withholding his principal treasures and giving charity for the sakeof social interest for the common good. In changing the status of waqfproperty, the turn of the object and the purpose of the waqf are verystrict in Syafi'i's Imam, however, on the basis of an emergency and theprinciple of maslahat, among jurists like Imam Hanafi, the change canbe made, So that the benefits of endowments that continue to continueas shadaqoh fingers, not mubadzir because it is damaged, does notwork anymore and so forth. With that change, the status of the objectas a waqf property is essentially undamaged.This research is basically aimed to know the view of Imam Syafi'i andImam Hanafi regarding the change of wakaf's property status, itcan be understood that regarding the change of wakaf wealth statusaccording to Imam Syafi'i it is said that the wakaf property that isnot working anymore still can not be sold, Exchanged, replaced andtransferred, except in a state of necessity the wakaf property can beexchanged or sold. Whereas Madzhab Hanafi is of the opinion that thewaqf objects that have been or are not functioning anymore whichis no longer in accordance with the allocation, it may sell, change,replace or move the wakaf objects, in order to function or bringmaslahat in accordance with the purpose of waqf, or to obtain moremaslahat Great for the public interest, especially the Muslims.